Internet Resources for Leisure and Tourism - Theobald, William; Dunsmore, H. E. (Routledge, 1999)
Internet Resources for Leisure and Tourism is designed to allow students, academics and practitioners within the leisure and tourism fields to get the very most out of the World Wide Web, helping them track down and fully exploit the most useful resources available. This book includes pointers on how to find and utilise, among other things: the latest economic statistics and demographics, information about government agencies and their programs, the content of universities' websites, up-to-the-minute statistics on visitor arrivals and departures, information on forthcoming meetings and conferences, and details of contents in periodicals.Features include: details of interesting sites for content, design and / or specific information notes emphasizing important information about a site shortcuts and easy-to-use methods for performing functions a wide variety of Internet topics - from how to find a provider to how to compress and decompress files that you download. The book is now updated and supported by a new companion website which provides the reader with regular updates about the latest online developments - thus continually keeping them up to speed in what is an exceptionally fast-moving medium.